Un converti convaincu, repentant et asexué ? (Anti-)Stéréotypes sur le Juif errant dans les romans français du XXe siècle - Kamiński, Paweł (Romanica Silesiana, 2021)
The present article seeks to analyse the figure of the Wandering Jew in five 20thcentury French novels (Carnet de route du Juif errant by Alexandre Arnoux, Les Entretiens d’Ahasvérus by Louis de Launay, Marches du Juif errant by Henry-Jacques, Jésus raconté par le Juif errant by Edmond Fleg and Histoire du Juif errant by Jean d’Ormesson). Its main goal is to answer the question to what extent the original image of the Jew is reproduced in the abovementioned prose works. In order to carry out his plan, the author takes into account the crucial and stereotypical characteristics which constitute the very nature of the Jewish vagabond. He tries then to point out major differences between the five novels and the popular version of the Ahasverian legend. The study of those elements shows that contemporary texts related to the immortal man break off with the traditional version of the legend and thus bear testimony of the so-called “death of the myth”.